BECOMING A FORENSIC PSYCHOLOGIST - DeMatteo, David, 1972-; FAIRFAX-COLUMBO, JAYMES; DESAI, ALISHA ([S.l.] : ROUTLEDGE, 2020)
The paths to becoming a forensic psychologist are numerous and varied. Becoming a Forensic Psychologist provides insight into the process of pursuing a career in forensic psychology, from an introduction to the field itself to graduate school and beyond. This comprehensive guide extends beyond mere definitions and overviews to discuss tips, strategies, and questions to ask at every step of the way to becoming a forensic psychologist. Told from the perspectives of individuals at different stages in their career, this book provides up-to-date information about existing forensic psychology programs and resources to assist aspiring forensic psychologists in career decision-making. Additional sidebars define key terms, highlight important court decisions that shaped the field of forensic psychology, and provide interesting facts about the field. This book will help any individual pursuing a career as a forensic psychologist, including those about to start college who are narrowing their career interests, graduate students, and those already in the field of psychology who are considering a career shift.
OCLC-licensed vendor bibliographic record.
Keywords: PSYCHOLOGY / General; PSYCHOLOGY / Forensic Psychology; Forensic psychology -- Vocational guidance